(untitled) (Progress Annals: Journal of Progressive Research, 2023)
Medicines discovery has come a long way since our ancient ancestors from the Neanderthals to the people of Mesopotamia, Egypt, Greece, and China used herbal remedies to treat ill people. In medieval times, the quest for the elixir of life was pursued by alchemists, but it is the scientists of the past 100-150 years who have had success in translating laboratory-based discoveries into drugs that have saved countless millions of lives (Sneader, 2005)1. The German stock market collapsed in 1873 and it was during the recovery period that the upsurge in the economy lead to an expansion of chemical and electrical industries. The significant investment in the manufacture of Synthetic dyes soon put Germany well ahead of all its competitors. As a consequence, German chemists did not only become very influential in the field of organic chemistry, but also led to the rise of the German pharmaceutical industry. Central to this industry was leading manufacturers, including F. Bayer Company and Farbenfabriken Hoechst, who realized that their chemists researching and developing dyes also had the potential to Produce new medicines (Sneader, 2005). One such scientist was Paul Ehrlich. Ehrlich was fascinated by colorful dyes and their capacity to interact with histological and cellular structures.Over several decades, he benefited from chemical companies that provided hundreds to thousands of new dyes for his research.